Asian Versus Non-Asian Outcomes in Nasopharyngeal Carcinoma: A North American Population-based Analysis. (December 2016) - Hamilton, Sarah N.; Ho, Cheryl; Laskin, Janessa; Zhai, Yongliang; Mak, Paul; Wu, Jonn
Abstract : Objectives: The effect of ethnicity on nasopharyngeal cancer (NPC) outcomes is unclear. This retrospective analysis examines survival and the impact of concurrent chemoradiation (chemoRT) among Asian and non-Asian patients. Methods: Subjects included 380 consecutive patients with NPC treated at a Canadian institution from 2000 to 2009. Five-year Kaplan-Meier progression-free survival (PFS), disease-specific survival (DSS), and overall survival (OS) were compared between Asian (n=279) and non-Asian (n=101) subjects. Multivariable analysis was performed using Cox regression modeling. Two-variable interaction terms with concurrent chemoRT were used to examine whether concurrent chemoRT conferred different effects among subgroups. Results: Asian subjects presented with earlier stage ( P =0.005), were younger, had better performance status, and were less likely smokers (all P <0.001). Survival among Asian versus non-Asian subjects with stage I/II NPC were: PFS 68% versus 59% ( P =0.04), DSS 87% versus 77% ( P =0.08), and OS 84% versus 74% ( P =0.003). Corresponding rates with stage III/IVA/IVB disease were PFS 49% versus 42% ( P =0.12), DSS 72% versus 46% ( P =0.001), and OS 70% versus 44% ( P <0.001). On multivariable analysis, Asian ethnicity, age below 65 years, ECOG performance status 0-1, early stage, staging MRI use, and concurrent chemoRT were associated with improved DSS and OS ( P <0.05). On testing interactions with concurrent chemoRT, Asian versus non-Asian ethnicity was significant (hazard ratio 3.9), suggesting that concurrent chemoRT conferred more benefit among non-Asian compared with Asian subjects. Conclusions: In this population-based study, Asian ethnicity was associated with improved DSS and OS. Concurrent chemoRT conferred more benefit among non-Asian compared with Asian subjects.